TARIK PASAR, KREASI NILAI DAN KEUNIKAN SUMBER DAYA UNTUK MENINGKATKAN KEUNGGULAN BERSAING SERTA IMPLIKASINYA TERHADAP KINERJA RUMAH SAKIT UMUM SWASTA DI JAWA BARAT - Novi Kadarini Rahayu (Coopetition : Jurnal Ilmiah Manajemen, 2019)
The hospital industry is need time solely the provision of services, but the hospital industry has become the realm of commercial. The high demand for hospital services and the new regulation on the establishment of hospital raise the attractiveness’s hospital. This research to verify the influence of market attractiveness, value creation with uniqueness of resources on competitive advantage of private general hospitals in the West Java, both partially and simultaneously and its impact on hoshospital performance. The findings reveal that the market attractiveness, value creation with uniqueness of resources affect the competitive advantage simultaneously. Meanwhile, partially, among these three variables, the value creation does not affect the competitive advantage. Additionally, through a competitive advantage, the market attractiveness, the value creation, also the uniqueness of the resources affect the performance. We suggest that the private general hospitals in West Java optimize value creation, create uniqueness of resources, enhance competitive advantage also gain better performance. We recommend further research for involving other variables, such as leadership style or organization behavior, in order to strengthen the influence of market attractiveness, uniqueness of resources on competitive advantage also performance of the private general hospitals in West Java.